The poetics of ancient and classical Arabic literature : Orientology - Duraković, Esad (Culture and civilisation in the Middle East, 2015)
Through analysing ancient and classical Arabic literature, including the Qur'an, from within the Arabic literary tradition, this book provides an original interpretation of poetics, and of other important aspects of Arab culture. Ancient Arabic literature is a realm of poetry; prose literary forms emerged rather late, and even then remained in the shadow of poetic creative efforts. Traditionally, this literature has been viewed through a philologist's lens and has often been represented as 'materialistic' in the sense that its poetry lacked imagination. As a result, Arabic poetry was often eva.